2007
DOI: 10.1080/00016480701242469
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of migraine in patients with Ménière's disease

Abstract: Age of onset of episodic vertigo or fluctuating hearing loss was significantly lower in patients with MMD (mean +/- 1.96*SE = 37.2 +/- 6.3 years) than in those with MD (mean +/- 1.96*SE = 49.3 +/- 4.4 years). Concurrent bilateral aural symptoms and hearing loss were seen in 56% of MMD and 4% of MD patients. A family history of episodic vertigo was seen in 39% of MMD and 2% of MD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
3
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 18 publications
3
56
3
2
Order By: Relevance
“…Migraine was twice as high in a group of 78 patients with unilateral or bilateral MD (based on the American Academy of Otolaryngology criteria), than in an ageand sex-matched control group (56% vs. 25%, p<0.001) [ 51 ]. Migraine leads to a greater susceptibility of developing MD, as suggested by a study in which MD patients had an earlier onset of symptoms and a greater frequency of bilateral hearing loss when they also had migraine [ 15 ].…”
Section: Menière's Diseasementioning
confidence: 92%
“…Migraine was twice as high in a group of 78 patients with unilateral or bilateral MD (based on the American Academy of Otolaryngology criteria), than in an ageand sex-matched control group (56% vs. 25%, p<0.001) [ 51 ]. Migraine leads to a greater susceptibility of developing MD, as suggested by a study in which MD patients had an earlier onset of symptoms and a greater frequency of bilateral hearing loss when they also had migraine [ 15 ].…”
Section: Menière's Diseasementioning
confidence: 92%
“…A link has been demonstrated between migraine and MD, 9,10 and it has even been suggested that MD develops as a complication of migraine-associated symptoms. 11 The overrepresentation of migraine among patients with MD might also be explained by migraine-associated vertigo, mimicking MD. 12 Anticipation, a phenomenon in which the symptoms of an inheritable disorder become apparent at an earlier age as they are passed on to the next generation, has also been described in MD.…”
mentioning
confidence: 99%
“…Finally, it has been reported that patients with Meniere's disease suffered higher prevalence of migraine and Meniere's disease patients with migraine suffered more severe vertigo or hearing loss Fig. 2 Relative risks of co-morbidities among cases of interest and the remaining migraine cases for the study period of 24 months before the index date (blue bars), and for the study period of 12 months after the index date (red bars) (color figure online) (Cha et al 2007). Again, the results from our populationbased study are in conformity with these findings.…”
Section: Otolaryngologymentioning
confidence: 99%